Penerapan Media Pembelajaran Berbasis Animasi Flash Pada Mata Pelajaran Rangakain Listrik di SMK Negeri 1 Padang - Juliwardi, Ilham; Ardiansyah, Muhammad; Suhendra, Rivansyah; Walid, Muhammad; Astrianda, Nica (Jurnal Teknologi Informasi, 2022)
This research is oriented to the learning outcomes of students who have not yet reached the KKM in the subject of electrical circuits for class X TITL at SMKN 1 Padang. Many factors affect the low student learning outcomes such as the learning process using conventional methods and the media used by the teacher in learning is a module and only uses the blackboard. Based on these factors, research is conducted in the form of experiments to improve student learning outcomes by using media-based flash animation learning media. The method used in this research is quasi-experimental with Pretest-Posttest One Group Design. The subjects of this study were students of class X SMKN 1 Padang semester January-June 2016, which amounted to 31 students. Collecting data in this study using a test (Pretest-Posttest), namely objective questions. The test questions used were tested first to determine the validity, reliability, level of difficulty, and discriminating power of the questions. Based on the results of the study obtained 25 items. The results showed that there was an increase in student learning outcomes of class X TITL SMKN 1 Padang in the subject of Electrical Engineering. The increase occurred at a high level (0.71) where 18 students were at a high level and 13 other students were at an increasing level. Based on the results of the study, it can be concluded that the application of flash animation media on electrical circuit subjects for class X TITL SMKN 5 Padang can improve student learning outcomes at a high level (0.71).